Effect of Smartphone Addiction on Academic Performance; Mediation of Self-Regulation and Bedtime Procrastination - Raja Zohaib Ghafoor, Sundus Nawaz, Tehreem Zahra, Tehreem Abdul Hakeem, (Pakistan Journal of Medical & Health Sciences, 2022)
This study examines the effect of smartphone addiction on the academic performance of medical students with the mediating role of self-regulation and bedtime procrastination. The framework of this study is based on social cognitive theory. Data was collected through an adopted questionnaire from the medical students at different institutes in Pakistan. A survey questionnaire was distributed among 300 students however 260 students participated and returned it. SmartPLS3 was used to analyze the data collected from respondents. Results showed that smartphone addiction is not negatively associated with academic performance. Similarly, smartphone addiction is not inversely associated with self-regulation. Furthermore, results showed a positive relationship between self-regulation and academic performance, a positive relationship between smartphone addiction and bedtime procrastination, and a negative relationship between bedtime procrastination and academic performance. Moreover, bedtime procrastination mediates the association between smartphone addiction and academic performance. Contrary to our expectations, self-regulation did not mediate the association between smartphone addiction and academic performance. Implications of research are discussed. Keywords: Smartphone addiction, Academic performance, Self-regulation, Bedtime procrastination